Pendekatan Hukum Islam Bagi Penerima Obat Gratis ARV di RSUP M.Djamil Padang dalam Mencegah Penularan HIV-AIDS (Jurnal Hukum Islam, 2019)
The patients of HIV-AIDS tend to commit deviant behavior, such as homosexual, bisexual, drugs abuse, and sex workers, though there are other causing factors. The government, however, has provided them with a free-of-charge treatment. This kind of treatment is allocated through one hospital in each province. The present study aims to investigate (1) the objective conditions of HIV-AIDS patients receiving antiretroviral (ARV) treatment at M.Djamil General Hospital (RSUP) Padang, (2) various treatments provided to the patients in the perspective of Islamic law, and (3) the free-of- charge ARV treatment received by the patients from the Islamic law perspective. Designed in a research-based community service, the study employed four strategies, namely: planning, action, observation, and reflection. The data were analyzed descriptively with data reduction, display, and conclusion verification. The findings promote that firstly, the objective conditions of HIV-AIDS patients receiving the ARV treatment at the M.Djamil RSUP Padang until December 2018 comprised 1805 people. They were mainly infected with HIV-AIDS through homosexual and bisexual behavior, the use of drug syringes, and prostitution. After receiving the ARV treatment, they still committed the deviant behavior. Secondly, practically, their behavior was categorized into hudud (penal presciptions) and could not be addressed a punishment for the perpetrators since it was not stipulated in regulations. Thus, taubat (repentance) approach is fostered to deal with.